1. The Lovozero Minerals-Nenadkevichite, Gerassimovskite and Tundrite- from Ilímaussaq, South Greenland. - Semenov, E. I.; Kazakova, M. E.; Aleksandrova, R. A. (Meddelelser om Grønland, 1967)
Nenadkevichite NaCaTiNbSi4O14.4H2O, gerassimovskite NbTi(OH)9 and tundrite Na2Ce2TiSiO8. 4H2O, which until now have been found only in the Lovozero alkaline massif in the Kola peninsula have also been found in the nepheline-sodalite syenites of the Ilímaussaq massif (South Greenland). Nenadkevichite and gerassimovskite occur in hydrothermal veins in the poikilitic sodalite syenites (naujaites) as alteration products of epistolite. Tundrite was found in pegmatites in nepheline syenites (kakortokites). A new formula of tundrite is suggested.